2017
DOI: 10.1177/0886260517696870
|View full text |Cite
|
Sign up to set email alerts
|

College Sexual Assault and Campus Climate for Sexual- and Gender-Minority Undergraduate Students

Abstract: Sexual- and gender-minority (e.g., lesbian, gay, bisexual, and transgender) undergraduate students are at greater risk for sexual assault victimization than their cisgender (i.e., nontransgender) heterosexual peers. However, few studies have examined how social environments affect sexual assault victimization among sexual- and gender-minority undergraduate students. Nevertheless, this research area was identified as a priority by the Institute of Medicine as well as President Barack Obama’s White House Task Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 18 publications
5
74
0
2
Order By: Relevance
“…Apart from the institutional validation, the research counted with an Advisory Board which supervised, followed-up and advise the research team in three different phases: approbation of the literature review, eldwork plan and preliminary results of the study. This board was composed by members of the LGBTQI + community, university students and representatives of active organizations for LGBTQI + rights of the territory 4 . Their belonging to the targeted community was due to the need of including the voices of the end-users of the research throughout the whole process of the research.…”
Section: Ethical Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the institutional validation, the research counted with an Advisory Board which supervised, followed-up and advise the research team in three different phases: approbation of the literature review, eldwork plan and preliminary results of the study. This board was composed by members of the LGBTQI + community, university students and representatives of active organizations for LGBTQI + rights of the territory 4 . Their belonging to the targeted community was due to the need of including the voices of the end-users of the research throughout the whole process of the research.…”
Section: Ethical Validationmentioning
confidence: 99%
“…Research have shown that transgender people are the most probable to have di culties and more probabilities to suffer violence or discrimination at HEI's (4)(5)(6). This form of vulnerability in the university context is even more disturbing when the results show the complexity and accumulation of forms of violence that only transgender studies suffer.…”
Section: Transgender Vulnerability In the Con Ictmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical support for this theory in examining vulnerability for sexual violence is building. For example, experiences of discrimination mediate vulnerability for dating violence in bisexual young adults (Martin-Storey & Fromme, 2017), perceived inclusion of LGBTQ people is related to lower rates of sexual violence on college campuses (Coulter & Rankin, 2017), and individual feelings of connectedness to the LGBTQ community are related to lower individual vulnerability for violence (Murchison et al, 2016).…”
Section: Minority Stress Theorymentioning
confidence: 99%
“…Research finds, for example, that white female students are less likely to intervene to prevent a sexual assault of a Black female victim then is the case when the victim is white (Katz, Merrilees, Hoxmeier & Motisi, 2017). Coulter and Rankin (2017) found that LGBT students who attend schools that rank lower on measures of LGBT student inclusion report higher rates of sexual assault than do students who attend schools that are more inclusive.…”
Section: Campus Climatementioning
confidence: 99%